PERAN ETIKA SOSIAL DALAM KEHIDUPAN DAN PELAYANAN GEREJA - Ketlin Yolanda Lende; Serlin Padama; Wandes Filmon Aryance Tally; Eldy Thimotius Hekboy (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
This article aims to examine the role of social ethics in life and in the dynamics of the Church’s real ministry as a manifestation of contextual and transformative Christian faith. The Church in its entirety is called not only as a spiritual community, but also as a moral agent that brings the values of the Kingdom of God into this increasingly complex social reality. Using a qualitative approach through literature study, this research then examines how Christian social ethics plays a role in shaping the orientation of the Church’s ministry in responding to issues of injustice, poverty, moral crisis, and social realities that are quite preoccupying to many elements. Theological reflections based on Matthew 25:35-40 then became a reference in understanding the Church’s calling to continue serving Christ through service to others, especially marginalized groups. The results of the study show that Christian social ethics, in its function as a bridge between faith and practice, is a means of renewing personal spirituality, strengthening the integrity of the Church’s ministry, and encouraging social transformation that is just. Thus, the Church’s ministry oriented towards the application of social ethics is not merely a philanthropic act, but a tangible, prophetic, and living testimony of faith that is relevant in the midst of the dynamics of modern society today.